Nitrogen-Doped Graphene via In-situ Alternating Voltage Electrochemical Exfoliation for Supercapacitor Application - Jing, Mingjun; Wu, Tianjing; Zhou, Yazheng; Li, Xilong; Liu, Yong (Frontiers in Chemistry, 2020)
Doping heteroatom, an effective way to enhance the electrochemical performances of graphene, has received wide attention, especially related to nitrogen. Alternating voltage electrochemical exfoliation, as a low cost and green electrochemical approach, has been developed to construct in-situ N-doped graphene (N-Gh) material. The N-Gh presents a much higher capacity than that of pure graphene prepared via the same method, which might be attributed to the introduction of nitrogen, which has much more effects and a disordered structure. As-prepared N-Gh exhibits a low O/C ratio that is helpful in maintaining high electrical conductivity. And the effects and disorder structure are also conductive to reduce the overlaps of graphene layers. A symmetric supercapacitor assembled with N-Gh electrodes displays a satisfactory rate behavior and long cycling stability (92.3% retention after 5,000 cycles).